2019
DOI: 10.1128/aac.02140-18
|View full text |Cite
|
Sign up to set email alerts
|

Small IncQ1 and Col-Like Plasmids Harboring bla KPC-2 and Non-Tn 4401 Elements (NTE KPC -IId) in High-Risk Lineages of Klebsiella pneumoniae CG258

Abstract: Col-like plasmids harboring bla KPC-2 and non-Tn4401 elements (NTE KPC-IId) in high-risk lineages of Klebsiella pneumoniae CG258.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 15 publications
4
17
0
Order By: Relevance
“…Over the last 5-year period, IncQ1 plasmids carrying bla KPC-2 have been reported in several different pathogens in Brazil including Klebsiella quasipneumoniae (1 isolate, BSI), K. pneumoniae ST340 (CC258) (1 isolate, no clinical data), and Pseudomonas aeruginosa ST2584 (1 isolate, BSI), as shown in Fig. 3 ( 29 31 ). This current outbreak added a further six additional cases and suggests that IncQ1 plasmids can act as efficient bla KPC-2 carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last 5-year period, IncQ1 plasmids carrying bla KPC-2 have been reported in several different pathogens in Brazil including Klebsiella quasipneumoniae (1 isolate, BSI), K. pneumoniae ST340 (CC258) (1 isolate, no clinical data), and Pseudomonas aeruginosa ST2584 (1 isolate, BSI), as shown in Fig. 3 ( 29 31 ). This current outbreak added a further six additional cases and suggests that IncQ1 plasmids can act as efficient bla KPC-2 carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Nicoletti et al (2015) 41 identified the bla KPC gene inserted into an IncQ plasmid in K. pneumoniae. Cerdeira et al (2019) 16 detected two isolates of K. pneumoniae that were resistant to carbapenems and had the bla KPC gene inserted into IncQ plasmids. According to Smalla et al (2000) 27 , IncQ is a small plasmid that can vary between 5.1-14.2 kb in size, and it can be found in several host bacterial cells.…”
Section: /8mentioning
confidence: 99%
“…Klebsiella pneumoniae carbapenemase (KPC) has become endemic in several countries and is frequently detected in K. pneumoniae isolates from Brazilian hospitals 1 , 13 , 14 , 15 , 16 , 17 . The bla KPC gene is often located on the transposon Tn4401 (Eilertson et al 18 ), which has been found in several transferable plasmids 4 , 19 , 20 , which ensures its dispersion among Klebsiella species and other genera of Gram-negative bacteria (Belder et al 21 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…International genetic contexts of bla CTX-M-14 (ISEcp1-bla CTX-M-14 -IS903D) (Lartigue, Poirel, & Nordmann, 2004) Regarding other plasmids identified in this study, IncN and IncHI2 have been related to the spread of bla CTX-M-1 and bla CTX-M-9 , respectively, and IncQ1 or IncX plasmid has been responsible by dissemination of carbapenemase encoding genes (Cerdeira et al, 2019;Mollenkopf et al, 2017;Paul et al, 2017;Zhao & Hu, 2013).…”
Section: Re Sults and Discussionmentioning
confidence: 80%